Autothermal CaO looping biomass gasification to increase process energy efficiency and reduce ash sintering. (1st October 2020) - Zhang, Shuming; Gao, Ningbo; Quan, Cui; Wang, Fengchao; Wu, Chunfei
Abstract: Biomass gasification is considered as a promising renewable energy technology to address climate change caused by greenhouse gas emissions and produce portable and clean energy products. However, biomass must be combusted in the traditional gasification to maintain the process, while excessive gasification temperature will lead to ash sintering, resulting in the shutdown of the equipment. Autothermal biomass gasification is directly maintained by carbonation reaction, which can maximize the production of combustible gas and reuse carbon dioxide in the flue gas. Lab-scale results indicated that similar H2 yield can be obtained via Auto-CaL-Gas technology at lower operating temperatures. Moreover, H2 concentration increased by 23.29% at 650 °C with CaO than at 750 °C without CaO, and 14.11% at 550 °C with CaO than at 650 °C without CaO, respectively, thus saving energy consumption and improving total energy efficiency in the biomass gasification process.